A REVIEW OF THE THERAPEUTIC CHARACTERISTICS OF CAMEL URINE - Alkhamees, Osama A.; Alsanad, Saud M. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: The therapeutic use of camel urine has been known for centuries, with evidence of its use for medicinal purposes found in early folklore. It has been used to cure different diseases; however, the significant therapeutic benefits of urine have yet to undergo rigorous scientific evaluation. In this review, a summary of the scientific evidence that supports these therapeutic actions has been presented. Materials and methods: A literature search of different electronic databases including PubMed, Medline, SCOPUS, Web of Knowledge, and Google Scholar were conducted to identify published studies exploring the therapeutic effects of camel urine. ‘Camel’ and ‘Urine’, ‘Medicinal properties’, ‘Natural products’ were entered into the databases as key words. Reference lists of published reviews retrieved by the search were also searched to identify relevant papers. Result: There have been several laboratory and limited clinical studies providing evidence of the therapeutic effects of camel urine in the treatment of cancer, viral hepatitis and other viral, bacterial and parasitic infections. Therapeutic uses in the cardiovascular system have also been discovered, with regard to platelet and fibrinolytic actions. Conclusion: The exploration of the use of camel urine is of great interest to determine the efficacy of this practice, as well as the safety of the patients being treated. This review presented the benefits of camel urine, which were commonly drawn from small laboratory studies. Therefore, many more preclinical and clinical studies are needed to examine the efficacy and safety of the use of camel urine in in the treatment of disease.